2022
DOI: 10.3390/brainsci12070829
|View full text |Cite
|
Sign up to set email alerts
|

Micro-RNAs from Plasma-Derived Small Extracellular Vesicles as Potential Biomarkers for Tic Disorders Diagnosis

Abstract: Tic disorders (TDs) are a series of childhood neuropsychiatric disorders characterized by involuntary motor and/or vocal tics and commonly comorbid with several other psychopathological and/or behavioral disorders (e.g., attention deficit hyperactivity disorder and obsessive–compulsive disorder), which indeed aggravate clinical symptoms and complicate diagnosis and treatment. Micro-RNAs (miRNAs) derived from small extracellular vesicles (sEVs) have been recognized as novel circulating biomarkers of disease. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…MiR-25 was reported to be involved in epilepsy, Parkinson's disease, cerebral ischemia, multiple sclerosis, panic disorder, alexithymia, and tic disorders (Guo et al, 2014;Zhang et al, 2016;Nuzziello et al, 2018;Min et al, 2019;Van der Auwera et al, 2022; Wang et al, 2022;Zhou and Qiao, 2022). The present study demonstrated that miR-25 might also be associated with schizophrenia, further confirming the role of miR-25 in neuropsychiatric diseases and suggesting that miR-25-3p might be a potential therapeutic target or a diagnosis biomarker of schizophrenia.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…MiR-25 was reported to be involved in epilepsy, Parkinson's disease, cerebral ischemia, multiple sclerosis, panic disorder, alexithymia, and tic disorders (Guo et al, 2014;Zhang et al, 2016;Nuzziello et al, 2018;Min et al, 2019;Van der Auwera et al, 2022; Wang et al, 2022;Zhou and Qiao, 2022). The present study demonstrated that miR-25 might also be associated with schizophrenia, further confirming the role of miR-25 in neuropsychiatric diseases and suggesting that miR-25-3p might be a potential therapeutic target or a diagnosis biomarker of schizophrenia.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies showed that miR-25 is involved in the pathogenesis of various diseases, such as acute myocardial infarction, left ventricular hypertrophy, heart failure, diabetes mellitus, diabetic nephropathy, tubulointerstitial nephropathy, and asthma bronchiale (Sárközy et al, 2018). Moreover, miR-25 was found to play a critical role in the pathogenesis of a range of neuropsychiatric diseases, including epilepsy (Li et al, 2020), Parkinson's disease (Chen et al, 2020), cerebral ischemia (Guo et al, 2014;Zhang et al, 2016;Zhou and Qiao, 2022), multiple sclerosis (Nuzziello et al, 2018), panic disorder (Min et al, 2019), alexithymia (Van der Auwera et al, 2022), and tic disorders (Wang et al, 2022). It was also reported that sarco(endo)plasmic reticulum Ca(2+) ATPase (SERCA2), a downstream target of miR-25, was elevated in the brains of patients with schizophrenia (Earls et al, 2012), suggesting a potential connection between miR-25 and schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Tics tend to be refractory to medical treatments and non-medical interventions, and most patients experience relapses that often persist into adulthood. Prediction and management of the risk for TD onset and relapse rely largely on biomarkers which, however, are severely lacking ( 4 ).…”
Section: Introductionmentioning
confidence: 99%